Techno-economic and environmental analyses of a biomass based system employing solid oxide fuel cell, externally fired gas turbine and organic Rankine cycle. (10th July 2019) - Roy, Dibyendu; Samanta, Samiran; Ghosh, Sudip
Abstract: This paper presents a techno-economic and environmental assessment of a biomass gasification based power plant integrating a solid oxide fuel cell module, an externally fired gas turbine and an organic Rankine cycle. The proposed biomass based system is nonparallel with the conventional biomass based power generation system because of biomass gasification, solid oxide fuel cell, externally fired gas turbine, organic Rankine cycle have been combined in a single system. The thermodynamic and economic performances of the plant have been investigated under the varying operating and design parameters. The maximum energetic and exergetic efficiencies of the system are computed to be 49.47% and 44.2%, respectively. Exergy analysis predicts that the biomass gasifier unit contributes highest amount of exergy destruction (38.91%) in terms of total exergy destruction of the system, followed by solid oxide fuel cell (21.24%) and secondary heat exchanger (13.11%). Economic analysis forecasts that the minimum levelized unit cost of electricity would be 0.086 $/kWh. A performance comparison with other conventional biomass based power generation systems shows that the proposed system exhibits better efficiency and cost of electricity than others. Environmental analysis predicts that the maximum CO2 emission reduction potential is computed to be 3564 t CO2 /year compared to the fossil fuel based power plant. Graphical abstract: Image 1 Highlights: A biomass fuelled solid oxide fuel cell based hybrid system has been developed. Thermodynamic, economic and environmental analyses have been conducted. System exhibits better performances than other biomass based plants. System yields highest efficiency of 49.47%, lowest cost of electricity of 0.086 $/kWh. Maximum CO2 emission can be reduced up to 3564 t CO2 /year.